“Effectiveness Of Self Instructional Leaflet On Breast Self Examination Among Women In Selected Rural Community, Chennai.” - Prof.Vahitha Mala.K; Dr.Kavinmozhi James; Mrs. Rejili Grace Joy.M; Prof. Punithavathi .I; Ms.Durga.G; Ms.Dhanlakshmi.L; Ms. Deepa.K; Ms.Divyabharathi.S (Revista Electronica de Veterinaria, 2024)
Breast cancer remains a major health concern for women globally, with early detection being crucial for survival. Breast self-examination (BSE) is a simple, cost-effective method for early detection; however, awareness and practice are often lacking, especially in rural areas. This study evaluated the effectiveness of a self-instructional leaflet in improving knowledge, attitudes, and practices regarding BSE in a rural community. A quasi-experimental, one-group pretest-posttest design was used, involving 100 women aged 35-50 from Thodukadu Rural Village, Chennai, selected via convenience sampling. Data were collected using a structured knowledge questionnaire, a 5-point Likert scale to assess attitudes, and a practice questionnaire. Pretest results showed that 92% of participants had inadequate knowledge, and 84% had poor BSE practice. Posttest results demonstrated significant improvement: 66% of participants gained adequate knowledge. Regarding attitudes, the pretest results showed that 31% of participants had an inadequate attitude, while 69% had a moderately adequate attitude. In the posttest, the majority (93%) had an adequate attitude, while 7% had a moderately adequate attitude. Additionally, 72% of participants practiced BSE effectively.The leaflet proved to be an effective educational tool, though no significant association was found between demographic factors and BSE outcomes. The study emphasizes the need for more educational interventions to enhance BSE awareness in underserved areas.